Bone evaluation in paediatric chronic kidney disease: clinical practice points from the European Society for Paediatric Nephrology CKD-MBD and Dialysis working groups and CKD-MBD working group of the ERA-EDTA. Issue 3 (2nd November 2020) - Bakkaloglu, Sevcan A; Bacchetta, Justine; Lalayiannis, Alexander D; Leifheit-Nestler, Maren; Stabouli, Stella; Haarhaus, Mathias; Reusz, George; Groothoff, Jaap; Schmitt, Claus Peter; Evenepoel, Pieter; Shroff, Rukshana; Haffner, Dieter; et al.
Abstract: Mineral and bone disorder (MBD) is widely prevalent in children with chronic kidney disease (CKD) and is associated with significant morbidity. CKD may cause disturbances in bone remodelling/modelling, which are more pronounced in the growing skeleton, manifesting as short stature, bone pain and deformities, fractures, slipped epiphyses and ectopic calcifications. Although assessment of bone health is a key element in the clinical care of children with CKD, it remains a major challenge for physicians. On the one hand, bone biopsy with histomorphometry is the gold standard for assessing bone health, but it is expensive, invasive and requires expertise in the interpretation of bone histology. On the other hand, currently available non-invasive measures, including dual-energy X-ray absorptiometry and biomarkers of bone formation/resorption, are affected by growth and pubertal status and have limited sensitivity and specificity in predicting changes in bone turnover and mineralization. In the absence of high-quality evidence, there are wide variations in clinical practice in the diagnosis and management of CKD-MBD in childhood. We present clinical practice points (CPPs) on the assessment of bone disease in children with CKD Stages 2–5 and on dialysis based on the best available evidence and consensus of experts from the CKD-MBD and Dialysis working groups of the European Society for Paediatric Nephrology and the CKD-MBD working group of the European Renal Association–European Dialysis and Transplant Association. These CPPs should be carefully considered by treating physicians and adapted to individual patients' needs as appropriate. Further areas for research are suggested.